P53/NANOG balance; the leading switch between poorly to well differentiated status in liver cancer cells - Ranjbar-Niavol, Fazeleh; Rezaei, Niloufar; Zhao, Ying; Mirzaei, Hamed; Hassan, Moustapha; Vosough, Massoud (Frontiers in Oncology, 2024)
Enforcing a well-differentiated state on cells requires tumor suppressor P53 activation as a key player in apoptosis induction and well differentiation. In addition, recent investigations showed a significant correlation between poorly differentiated status and higher expression of NANOG.Inducing the expression of NANOG and decreasing P53 level switch the status of liver cancer cells from well differentiated to poorly status. In this review, we highlighted P53 and NANOG crosstalk in hepatocellular carcinoma (HCC) which is regulated through mitophagy and makes it a novel molecular target to attenuate cancerous phenotype in the management of this tumor.